Design and analysis of two switch DC-DC converters for E-vehicle applications - Kathiresan, Jayanthi; Jothimani, Gnanavadivel (International Journal of Applied Power Engineering (IJAPE), 2025)
A non-isolated DC-DC converter topology is proposed in this paper, which is distinguished by its superior performance and reduced component count in comparison to conventional converter designs. The suggested architecture is especially appropriate for applications demanding a large voltage step-up since it achieves an improved voltage conversion ratio and excellent efficiency. The addition of a voltage-boosting element, which is an inductor combined in series with a switching device, to the source side of a conventional boost converter is a unique feature of the suggested converter. To confirm the converter's operating features, a thorough theoretical analysis has been carried out, including stability and steady-state evaluations. In addition, a hardware prototype with a 200 V output and 100 W power rating was created in order to test the converter's functionality. With a peak efficiency of 94.3%, the prototype showed good agreement with analytical forecasts. The suggested converter is a viable option for renewable energy applications because of its high voltage gain, small size, and efficiency. This is especially true for solar systems and other distributed energy sources, where low component counts and high step-up ratios are preferred.